Synthesis of Thermally Spherical CuO Nanoparticles. (8th January 2014) - Tamaekong, Nittaya; Liewhiran, Chaikarn; Phanichphant, Sukon
Abstract : Copper oxide (CuO) nanoparticles were successfully synthesized by a thermal method. The CuO nanoparticles were further characterized by thermogravimetric analysis (TGA), differential thermal analysis (DTA), X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray spectrometry (EDS), and high resolution transmission electron microscopy (HRTEM), respectively. The specific surface area (S S A BET ) of CuO nanoparticles was determined by nitrogen adsorption. The S S A BET was found to be 99.67 m 2 /g (d BET of 9.5 nm). The average diameter of the spherical CuO nanoparticles was approximately 6–9 nm.